Saybrook, Conn., land records.
Photocopies of surveys of land near Saybrook, Conn., conducted for James Fitch.
Typewritten transcript also available, in part.
Positive and negative photocopies produced with permission of Jane G. Lewis.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Fitch, James, -- 1622-1702.; Saybrook (Conn.) -- Surveys; Connecticut -- Surveys